Penerapan pendidikan Islam di sekolah Islam terpadu - Huda, Miftahul (Maliki Interdisciplinary Journal, 2024)
Islamic education is a teaching process that transforms and forms individuals who are pious, have noble character, and have extensive knowledge in accordance with Islamic teachings. Which is guided by the highest sources of Islamic law, namely the Al-Qur'an and Hadith. The goal of Islamic education is the same as the goal of national education, namely to educate the nation and create a generation that is pious and brings Indonesian civilization. However, the reality on the ground has not been able to make this happen. Many problems arise related to education in Indonesia, especially in Islamic education. Therefore, teaching methods, curricula, and the application of Islamic education are needed that can realize these educational goals. Among them is the learning curriculum that is taught in the Integrated Islamic School Network (JSIT) as well as how to apply Islamic values ​​that have been taught and the system of teaching methods that are applied to students. The method used by the author in writing this article is to use a descriptive qualitative method. By looking for reading sources from literature studies (library research) through books or journals related to Islamic Education.